Zrównoważony rozwój w polityce regionalnej – przykład Strategii Województwa Zachodniopomorskiego do 2030 roku - Magdalena Kogut-Jaworska; Bogdan Wankiewicz (Ekonomiczne Problemy Usług, 2018)
Pursuing various policies by self-governmental institutions or agencies needs an orderly approach and co-ordination with European and national policies in order to set essential goals for the overall development strategy within the existing legal and organizational framework. When talking actions in this respect, self-governmental agencies should always have in mind the paradigm of the well-balanced economic, social and urban development. The paper introduces examples of core documents prepared at the national and regional levels, whose aim is to indicate the main assumptions for rational development, as well as the paper stresses the level of their cohesion in the context of pursuing the paradigm of sustainable development. The main research objective of the paper is to introduce the essence and scope of national and regional development strategies and to asses advantages and limitations related to their implementation.